Heart transplant outcomes in patients with Chagas cardiomyopathy in the United States. Issue 6 (3rd June 2018) - Benatti, Rodolfo D.; Al‐Kindi, Sadeer G.; Bacal, Fernando; Oliveira, Guilherme H.
Abstract: Background: Chagas cardiomyopathy (CC) is one of the chronic manifestations of Trypanosoma cruzi ( T. cruzi ) infection and is among the leading reasons for heart transplantation (HT) in Latin America. Chagas disease is also present in areas with large Hispanic communities in the United States. Our objective is to evaluate the outcomes of cardiac allograft recipients with the diagnosis of CC in the United States. Methods and Results: We identified 25 adult patients with CC and 15 930 with idiopathic dilated cardiomyopathy (IDCMP) who underwent HT between 1987 and 2015. CC patients were mostly Hispanics, had lower mean pulmonary artery pressure (23 vs 29 mm Hg, P  = .035) and lower BMI (24 vs 26, P  = .007). Patients with CC were more likely to be supported with a total artificial heart (TAH) as bridge to transplant ( P  = .009). There were no statistical differences for overall mortality and graft survival between CC and IDCMP cardiac allograft recipients. Induction therapy and mycophenolate mofetil (MMF) use were associated with higher rate of infection in Chagas patients. Conclusions: Heart transplantation recipients with CC diagnosis appear to have similar outcomes to IDCMP patients. Induction therapy and MMF use may be associated with higher risk of infection in CC patients who underwent transplantation.